New Integron-Associated Gene Cassette Encoding a 3-N-Aminoglycoside Acetyltransferase - Levings, Renee S. (American Society for Microbiology, 2005)
A fifth gene cassette containing an aacC gene, aacCA5, was found in an aacCA5-aadA7 cassette array in a class 1 integron isolated from a multiply drug resistant Salmonella enterica serovar Kentucky strain. The AacC-A5 or AAC(3)-Ie acetyltransferase encoded by aacCA5 is related to other AAC(3)-I enzymes and confers resistance to gentamicin.